Characterization and identification of Xanthomonas spp. isolated from infected brassicaceae and selection of potential xanthan gum producer - Khanom Simarani,; Nur Izlin Shafinaz Bokhari,; Haziqah Mohd Saleh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Xanthomonas spp. synthesize a complex exopolysaccharide called xanthan gum, which has significant commercial value. Xanthomonas-infected vegetables exhibiting typical spot symptoms were used in this study. Isolation was done by streaking the sample suspension on the Yeast Malt agar. A colony that resembled Xanthomonas spp. was purified before a simple phenotypic test and identified using BIOLOG and 16 rRNA sequencing. The screening was done based on their performance by fermentation in a shake flask, under controlled conditions. The yield and viscosity of xanthan gum produced from each bacterium were compared to Xanthomonas campestris PV. campestris strain ATCC33913. There were 411 wild types of Xanthomonas spp. successfully isolated and ten strains were selected for xanthan gum evaluation. The results showed, the xanthan production (g/L) varied from (1.57 - 8.24) with the yield of xanthan from 0.64 to 4.71 g/g biomass. Strain C206 produced the highest xanthan gum concentration (8.24±0.20 g/L) compared to others and the control strain, ATCC 33913 (2.27±0.10g/L). The highest yield of xanthan 4.71±0.18 (g/g biomass) was produced by strain C298 followed by strain C279 with 3.88±0.04 (g/g biomass). From our investigation, the production and yield of xanthan gum and the viscosity of the polymers were significantly dependent on the bacterial strain. Based on the stable viscosity and yield of xanthan produced, X. campestris C279 was selected for further studies on product optimization.